Relationships Between Neighborhoods, Physical Activity, and Obesity: A Multilevel Analysis of a Large Canadian City - Kristjansson, Elizabeth A.; Russell, Katherine; Billette, Jean-Michel; Sawada, Michael C.; Ali, Amira; Tremblay, Mark S.; Prud'homme, Denis; Prince, Stephanie A. (Université d'Ottawa | University of Ottawa, 2012)
In Canada, there is limited research examining the associations between objectively measured neighborhood environments and physical activity (PA) and obesity. The purpose of this study was to determine the relationships between variables from built and social environments and PA and overweight/obesity across 86 Ottawa, Canada neighborhoods. Individual-level data including self-reported leisure-time PA (LTPA), height, and weight were examined in a sample of 4,727 adults from four combined cycles (years 2001/03/05/07) of the Canadian Community Health Survey (CCHS). Data on neighborhood characteristics were obtained from the Ottawa Neighbourhood Study (ONS); a large study of neighborhoods and health in Ottawa, Canada. Binomial multivariate multilevel models were used to examine the relationships between environmental and individual variables with LTPA and overweight/obesity using survey weights in men and women separately. Within the sample, ~75% of the adults were inactive (<3.0 kcal/kg/day) while half were overweight/obese. Results of the multilevel models suggested that for females greater park area was associated with increased odds of LTPA and overweight/obesity. Greater neighborhood density of convenience stores and fast food outlets were associated with increased odds of females being overweight/obese. Higher crime rates were associated with greater odds of LTPA in males, and lower odds of male and female overweight/obesity. Season was significantly associated with PA in men and women; the odds of LTPA in winter months were half that of summer months. Findings revealed that park area, crime rates, and neighborhood food outlets may have different roles with LTPA and overweight/obesity in men and women and future prospective studies are needed.
Keywords: physical activity; Obesity; Ottawa, Canada; Park areas and obesity; Crime rates and obesity; Neighbourhood food outlets and obesity